Static compliance checking beyond separation of duty constraints. (2018) - Bo, Yang; Xia, Chunhe; Luo, Yang; Tang, Qing
Compliance requirements, such as separation of duty and binding of duty, have to be satisfied in many application domains. Existing compliance checking frameworks either have limited expressiveness or rely on model checking, which has small applicable range and low efficiency. To overcome these limitations, we improve high level expression separation of duty algebra to: 1) describe both SoD and BoD constraints to make it more expressive; 2) describe user-task relationship to perform compliance checking. In order to make the improved high level policy act on concrete process, we: 1) construct mapping rules to translate the improved high level policies to low level constraints described in description logic; 2) propose a reasoning framework to check for business process compliance. We report on the applicability of our approach via a case study.